ANALISIS KECENDERUNGAN LOGO DAN KEMASAN RESTORAN AYAM GEPREK DI KECAMATAN COBLONG - Lidwina Zita Dewi; Oki Hamka Suyatna (Wimba : Jurnal Komunikasi Visual, 2023)
Ordering food with Online Food Delivery (OFD) service is a common and popular activity amongst university students. Rice and chicken are one of the most popular menus, ayam geprek is one of them. The development of ayam geprek industries and OFD technology encourages every business owner to compete. One of the ways to survive is by building brand identity such as logo and designing a good packaging complemented by their own characteristic. Therefore, this research is done to learn the visual tendencies and the application on packaging design found in ayam geprek restaurants around Coblong District. Data is collected by comparing ten logos & packaging from restaurants with content analysis and descriptive analysis methods. The results show that there are similarities of visual elements found in few logos and packaging which applied with their own characteristics and uniqueness.